Investigação epidemiológica de um surto de gastroenterite Epidemiological investigation into an outbreack of gastroenteritis - Romeo Luiz Baldissera; Stela Nazareth Meneghel (Universidade de São Paulo, 1986)
Realizou-se investigação epidemiológica de um surto de gastroenterite em um navio da marinha brasileira. Foram atingidos 184 indivíduos, representando uma taxa de ataque de 72,7%. O quadro clínico prevalente foi febre, mal-estar, cefaléia, náuseas, vomitóse diarréia. Realizou-se um inquérito alimentar para averiguar a possível fonte de infecção. Foram isoladas Salmonellas do grupo C2 em 74 coproculturas (40,6%). Não foi possível estabelecer o veículo de transmissão do agente, ficando sob suspeição a água e alguns dos alimentos consumidos. An epidemiological investigation into an outbreak of gastroenteritis on a ship anchored in Rio Grande harbor was reported. One hundred and eighty four personns acquired the disease, with an attack rate of 72,7%. The cases accurred one day after the beginning of te trip and the clinical manifestations were fever, malaise, headache, nausea, vomiting and diarrhea. There were no deaths. Three hypotesis were formulated to explain the etiology: typhoid fever, insecticide intoxication, and food related disease. Alimentary enquiries showed high attack rates for some foods eaten at dinner on Sunday December 3rd. Laboratory tests were performed: Widal reaction, haemoculture, coproculture, food analysis and analysis of water from the ship's fresh water tanks. Salmonella serotype "emek" was found in 40.1% of the samples. The bacteriological analysis of the water showed proved it unfit for human consumption. The alimentary etiology, in the light of the clinical, epidemiological and laboratorial data, was confirmed. It was impossible to establish the transmission vehicle. Water and some food remained under suspicion.